Temporal variability and site specificity of thermomechanical weathering in a temperate climate - Gage, Henry J. M.; Nielsen, Julia P.; Eyles, Carolyn H. (Frontiers in Earth Science, 2024)
Thermomechanical processes caused by short- and long-term temperature fluctuations are a prevalent weathering mechanism on exposed rock walls. While many authors have explored the potential for thermomechanical weathering in alpine and polar regions, few have examined the effects of seasonality on weathering in temperate climates. This is pertinent as seasonal climatic conditions may influence both short-term temperature oscillations which produce incipient fractures and diurnal- to annual-scale cycles which propagate pre-existing fractures via thermal fatigue. In this study, three rock outcrops located along the Niagara Escarpment in Hamilton, Canada were monitored to examine changes in the thermal regime at the rock surface and within pre-existing fractures over a one-year period. Temperature was sampled in one-minute intervals, providing data at a fine temporal resolution. Our unique dataset demonstrates that the rock surface and fracture experience minute-scale temperature oscillations which magnify over time. Longer-term temperature cycles during the year are superimposed upon minute- and diurnal-scale fluctuations which likely augment weathering potential. This produces considerable thermal stress over the year which we estimate to be on the order of 18 GPa at the rock surface and 8 GPa in fractures. We also observed diurnal reversals of the temperature gradient between the rock surface and fracture which may further amplify crack propagation. Seasonality and site-specific characteristics interact to modify different components of the rockwall thermal regime. Vegetation shading has seasonal- and diurnal-scale impacts on the temperature gradient between the surface and fracture, and the amplitude of daily warming and cooling cycles. Aspect has a stronger influence on minute-scale temperature oscillations. Estimates of diurnal thermal stress indicate that the thermomechanical weathering potential is seasonally variable, but highest in the spring. Our findings demonstrate that in a temperate climate, rockwall thermal regimes experience variability across the gradient of temporal scale with strong seasonal effects.